REKAYASA INOVASI PENGEMBANGAN PEMASARAN PRODUK UMKM MASYARAKAT DESA SINDANG SARI - Novita Sari (MUHKAL, 2023)
Sindang Sari Village is one of the villages that has an individual medium-sized business activity unit that is not yet organized for marketing and product publication on digital media platforms, so it requires coaching and empowerment by students to build marketing alternatives that can help increase results. and the economy of SMEs and society. The method used is the development of science and technology as well as the practice of using online media starting with the use of Smartphones that can be well accessed by the MSME activist community. All forms of PKPM activities are carried out by observing to find out the background of the problems needed by village MSME activists. Results and impacts, these programs have been implemented well and play a role in increasing the results of improving the community's economy and acting as community skills towards online media.